Comparison General Anesthesia And Combined Scalp Block With Ropivacaine 0.5% On Mean Arterial Pressure, Heartrate And Fentanyl Consumption During Craniotomy. - Rudi Iskandar Suryadani; Hamzah Hamzah; Nancy Margarita Rehatta; Arie Utariani (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Surgical craniotomy such as skin incisions, head pinning, periosteal-dural contact, dura closure, bones and skin can cause of nociceptive stimulation. These actions are stimuli to the nerves that can stimulate stress response. The stress response to surgery is characterized by increased secretion of the pituitary hormone and activation of the sympathetic nervous system. Hypothalamic activation of the sympathetic autonomic nervous system results in increased secretion of catecholamines from the adrenal medulla and the release of norepinephrine from the presynaptic nerve terminal. Objectives: This study is a single blind experimental, 14 patients with ages 18-60 years physical status ASA (American Society of Anesthesiologists) 1-3, with elective craniotomy surgery. This study was divided into two groups of subjects, group A with seven craniotomy subjects with general anesthesia and group B with seven craniotomy subjects combined with scalp block using ropivacaine 0.5%. Data collected then analyzed with SPSS. We found a decrease in MAP (Mean Arterial Pressure) and heart rate in the scalp block group during scalp incision (MAP p=0.002; HR p=0.029), periosteal contact (MAP p=0.025; HR p=0.039) significantly, as well as the use of fentanyl during surgery was significantly decreased (p=0.0001). General anesthesia with scalp block is more effective in reducing the increase in MAP, heart rate and fentanyl consumption during craniotomy.